Women’s empowerment in rural community development: The case of barangay Buenavista in Tudela, Misamis Occidental - Trinidad, Eunice Tabitha B. (Animo Repository, 2023)
This thesis looks into women's empowerment in the local community of Barangay Buenavista in the municipality of Tudela, Misamis Occidental, using participant observation. This study focused on the experiences of women participating in the KALAHI-CIDSS PAMANA (KC-PAMANA) program. This program plays an important role in broadening the opportunities for inclusive development in the Philippines. The KC-PAMANA program serves as a platform for women, especially those in indigenous communities, to participate in and engage in community development projects. Based on previous studies and existing literature, development programs are deemed effective in empowering women because of the mechanisms and structures that give women roles and responsibilities and encourage their participation in community development. Even though development programs provide opportunities for women's participation, this study analyzed if the parameters set by the KC-PAMANA program provide a system that empowers the women participants of this program in Tudela. The key statements gathered from raw data were categorized into the three levels of developmental progression, which include 'awareness, confidence, and capability, as well as effectiveness and self-sustaining,' as proposed by Jupp et al. (2010) in their study of women's empowerment in rural Bangladesh communities. This research identified how community-driven development efforts play a part in women's empowerment, and focused on the perspectives of women on the factors that are empowering or disempowering. Through a series of dialogues, interviews, and observations, this study discovered that the mechanisms provided in the community-driven development activities contribute to both empowering and disempowering aspects. These empowering factors include the governance framework and community network, whereas the disempowering factors include the service delivery dynamics, lack of sustainable income, and social norms. This study also highlighted what empowerment means and how empowerment is understood by the women members which focused on five main themes including participation, collaborative decision making, capacity building, opportunity, and self-sufficiency. This study is a relevant contribution to the literature on empowerment as it highlights that empowerment is contextual and that its indicators are dynamic. Hence, women should be involved in identifying indicators and factors that affect their empowerment, as well as determine what works for them and what could be improved in the policy and implementation process. Key words: Women’s empowerment; participant observation; community development; KC-PAMANA; participation